ANTI FLOW GLASS HOLDER - RAO, B.VENKATESWARA; ASMA, MD.; RAJU, K.; KARTHIK, A.VENKATA; JYOSHITHA, A. (The journal of contemporary issues in business and government, 2021)
Project was based on the development of a stabilizing cup holder that can compensate forangular changes. The use of stabilizing mechanisms is an increasingly common practice in our everyday life technology. Pouring drinks in the cup/glass and carrying it from one place to other without spilling of drink from cup is more challenging task. Sudden movements or jerks may cause spills. It should not to be used with liquids that are hot enough to scald and should not be used in moving vechiles.To overcome this issue a stabilizing cup holder is required. The cup holder consists of an gyro sensor that measures the angular changes in three axes. The system was constructed to compensate angular changes with servo motors contolled by Arduino. In the system the gyro sensor detects the angular changes and instructions sent to the Arduino.